The Identification of Plant Growth Promoting Rhizobacteria from Thorny Bamboo Rhizosphere with 3% KOH Gram Test and Gram Staining Test - Muhammad Yusril Hardiansyah Muhammad Yusril Hardiansyah (International Journal of Applied Biology, 2020)
Plant Growth Promoting Rhizobacteria (PGPR) is a group of beneficial bacteria that actively colonize the rhizosphere and play an important role in enhancing root growth that impacts on plant growth, yields and land fertility. PGPR is very much found in the area around plant roots or rhizosphere especially thorny bamboo rhizosphere (Bambusa blumeana). The number of microorganisms contained in PGPR spiked bamboo rhizosphere makes it difficult to know what types of bacteria are the most dominant and most active in influencing plant growth. One method that can be used to identify microorganisms is by biochemical testing processes using the 3% gram KOH test method and gram staining test. This study aims to determine the use of the 3% gram KOH test method and gram staining test in identifying Plant Growth Promoting Rhizobacteria bacteria from thorny bamboo rhizosphere (Bambusa blumeana). This test is carried out at the Biofertilizer and Potential Microbial Laboratory, Ministry of Agriculture, Faculty of Agriculture, Hasanuddin University, Makassar and takes place from October to December 2019. The method of carrying out the test includes making the media nutrient agar (NA), pouring media, planting bacteria, identifying bacteria in 2 gram reaction methods, namely the gram reaction test using 3% KOH and using a simple coloring with methylen blue and lugol. The results obtained are the 3% gram KOH test method in testing the scratch method of all samples that have slime while the scatter method has 2 samples that have slime. Then the gram staining test method on staining with methylene blue and logol produces blue for the genus Pseudomonas which means gram positive and pink or purple for the genus Bacillus which means gram positive. So it can be concluded that the 3% KOH test method and gram staining test have optimum effect in detecting microorganisms.